Hadith #55 - Sahih al-Bukhari - Abu Mas'ud al-Ansari (Sahih al-Bukhari)
The Prophet (ï·º) said, âIf a man spends on his family (with the intention of having a reward from Allah) sincerely for Allahâs sake then it is a (kind of) alms-giving in reward for him.
Grade: Sahih

Hadith #90 - Sahih al-Bukhari - Abu Mas'ud al-Ansari (Sahih al-Bukhari)
Once a man said to Allahâs Messenger (ï·º) âO Allahâs Messenger (ï·º)! I may not attend the (compulsory congregational) prayer because so and so (the Imam) prolongs the prayer when he leads us for it. The narrator added: âI never saw the Prophet (ï·º) more furious in giving advice than he was on that day. The Prophet said, âO people! Some of you make others dislike good deeds (the prayers). So whoever leads the people in prayer should shorten it because among them there are the sick th
Grade: Sahih

Hadith #685 - Sahih al-Bukhari - Abu Mas'ud al-Ansari (Sahih al-Bukhari)
A man came and said, âO Allahâs Messenger (ï·º)! By Allah, I keep away from the morning prayer only because So and so prolongs the prayer when he leads us in it.â The narrator said, âI never saw Allahâs Apostle more furious in giving advice than he was at that time. He then said, âSome of you make people dislike good deeds (the prayer). So whoever among you leads the people in prayer should shorten it because among them are the weak, the old and the needy.â
Grade: Sahih

Hadith #687 - Sahih al-Bukhari - Abu Mas'ud al-Ansari (Sahih al-Bukhari)
A man came and said, âO Allahâs Messenger (ï·º)! I keep away from the morning prayer because so-and-so (Imam) prolongs it too much.â Allahâs Messenger (ï·º) became furious and I had never seen him more furious than he was on that day. The Prophet (ï·º) said, âO people! Some of you make others dislike the prayer, so whoever becomes an Imam he should shorten the prayer, as behind him are the weak, the old and the needy.â
Grade: Sahih

Hadith #1013 - Sahih al-Bukhari - Abu Mas'ud al-Ansari (Sahih al-Bukhari)
The Prophet (ï·º) said, âThe sun and the moon do not eclipse because of the death of someone from the people but they are two signs amongst the signs of Allah. When you see them stand up and pray.â
Grade: Sahih

Hadith #1027 - Sahih al-Bukhari - Abu Mas'ud al-Ansari (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âThe sun and the moon do not eclipse because of someoneâs death or life but they are two signs amongst the signs of Allah, so pray whenever you see them.â
Grade: Sahih

Hadith #1367 - Sahih al-Bukhari - Abu Mas'ud al-Ansari (Sahih al-Bukhari)
When the verses of charity were revealed, we used to work as porters. A man came and distributed objects of charity in abundance. And they (the people) said, âHe is showing off.â And another man came and gave a Sa (a small measure of food grains); they said, âAllah is not in need of this small amount of charity.â And then the Divine Inspiration came: âThose who criticize such of the believers who give in charity voluntarily and those who could not find to give in charity except what is
Grade: Sahih

Hadith #1368 - Sahih al-Bukhari - Abu Mas'ud al-Ansari (Sahih al-Bukhari)
Whenever Allahâs Messenger (ï·º) (p.b.u.h) ordered us to give in charity, we used to go to the market and work as porters and get a Mudd (a special measure of grain) and then give it in charity. (Those were the days of poverty) and today some of us have one hundred thousand.
Grade: Sahih

Hadith #2006 - Sahih al-Bukhari - Abu Mas'ud al-Ansari (Sahih al-Bukhari)
An Ansari man, called Abu Shuâaib, came and told his butcher slave, âPrepare meals sufficient for five persons, for I want to invite the Prophet (ï·º) along with four other persons as I saw signs of hunger on his face.â Abu Shuâaib invited them and another person came along with them. The Prophet (ï·º) said (to Abu Shuâaib), This man followed us, so if you allow him, he will join us, and if you want him to return, he will go back.â Abu Shuâaib said, âNo, I have allowed him (i.e.
Grade: Sahih

Hadith #2155 - Sahih al-Bukhari - Abu Mas'ud al-Ansari (Sahih al-Bukhari)
Allahâs Messenger (ï·º) forbade taking the price of a dog, money earned by prostitution and the earnings of a soothsayer.
Grade: Sahih

Hadith #2188 - Sahih al-Bukhari - Abu Mas'ud al-Ansari (Sahih al-Bukhari)
Whenever Allahâs Messenger (ï·º) ordered us to give in charity we would go to the market and work as porters to earn a Mudd (two handfuls) (of foodstuff) but now some of us have one-hundred thousand Dirhams or Diners. (The sub-narrator) Shaqiq said, âI think Abu Mas`ud meant himself by saying (some of us) .
Grade: Sahih

Hadith #2197 - Sahih al-Bukhari - Abu Mas'ud al-Ansari (Sahih al-Bukhari)
Allahâs Messenger (ï·º) regarded illegal the price of a dog, the earnings of a prostitute, and the charges taken by a soothsayer.
Grade: Sahih

Hadith #2360 - Sahih al-Bukhari - Abu Mas'ud al-Ansari (Sahih al-Bukhari)
There was an Ansari man called Abu Shuâaib who had a slave butcher. Abu Shuâaib said to him, âPrepare a meal sufficient for five persons so that I might invite the Prophet (ï·º) besides other four persons.â Abu Shuâaib had seen the signs of hunger on the face of the Prophet (ï·º) and so he invited him. Another man who was not invited, followed the Prophet. The Prophet (ï·º) said to Abu Shuâaib, âThis man has followed us. Do you allow him to share the meal?â Abu Shuâaib said, â
Grade: Sahih

Hadith #3071 - Sahih al-Bukhari - Abu Mas'ud al-Ansari (Sahih al-Bukhari)
The Prophet (ï·º) said, âthe sun and the moon do not eclipse because of the death or life of someone, but they are two signs amongst the Signs of Allah. So, if you see them, offer the Prayer (of eclipse).
Grade: Sahih

Hadith #3337 - Sahih al-Bukhari - Abu Mas'ud al-Ansari (Sahih al-Bukhari)
The Prophet (ï·º) said, âOne of the sayings of the prophets which the people have got, is. âIf you do not feel ashamed, then do whatever you like.â
Grade: Sahih

Hadith #4194 - Sahih al-Bukhari - Abu Mas'ud al-Ansari (Sahih al-Bukhari)
The Prophet (ï·º) beckoned with his hand towards Yemen and said, âBelief is there.â The harshness and mercilessness are the qualities of those farmers etc, who are busy with their camels and pay no attention to the religion (is towards the east) from where the side of the head of Satan will appear; those are the tribes of Rabi`a and Mudar.
Grade: Sahih

Hadith #4462 - Sahih al-Bukhari - Abu Mas'ud al-Ansari (Sahih al-Bukhari)
When we were ordered to give alms, we began to work as porters (to earn something we could give in charity). Abu `Aqil came with one half of a Sa` (special measure for food grains) and another person brought more than he did. So the hypocrites said, âAllah is not in need of the alms of this (i.e. Abu `Aqil); and this other person did not give alms but for showing off.â Then Allah revealed:â âThose who criticize such of the Believers who give charity voluntarily and those who could not fi
Grade: Sahih

Hadith #4801 - Sahih al-Bukhari - Abu Mas'ud al-Ansari (Sahih al-Bukhari)
Whoever recites two verses â¦ (text as in the following hadith)
Grade: Sahih

Hadith #4802 - Sahih al-Bukhari - Abu Mas'ud al-Ansari (Sahih al-Bukhari)
The Prophet (ï·º) said, âIf somebody recited the last two Verses of Surat Al-Baqara at night, that will be sufficient for him.â
Grade: Sahih

Hadith #4835 - Sahih al-Bukhari - Abu Mas'ud al-Ansari (Sahih al-Bukhari)
The Prophet (ï·º) said, âIf one recites the last two verses of Surat al-Baqarah at night, it is sufficient for him (for that night).â
Grade: Sahih

Hadith #4847 - Sahih al-Bukhari - Abu Mas'ud al-Ansari (Sahih al-Bukhari)
The Prophet (ï·º) said, âIf somebody recites the last two Verses of Surat al-Baqara at night, it will be sufficient for him.
Grade: Sahih

Hadith #5093 - Sahih al-Bukhari - Abu Mas'ud al-Ansari (Sahih al-Bukhari)
The Prophet (ï·º) pointed with his hand towards Yemen and said twice, âFaith is there,â and then pointed towards the East, and said, âVerily, sternness and mercilessness are the qualities of those who are busy with their camels and pay no attention to their religion, where the two sides of the head of Satan will appear,â namely, the tribes of Rablâa and Muqar.
Grade: Sahih

Hadith #5132 - Sahih al-Bukhari - Abu Mas'ud al-Ansari (Sahih al-Bukhari)
The Prophet (ï·º) prohibited taking the price of a dog, the earnings of a soothsayer and the money earned by prostitution.
Grade: Sahih

Hadith #5137 - Sahih al-Bukhari - Abu Mas'ud al-Ansari (Sahih al-Bukhari)
The Prophet (ï·º) said, âWhen a Muslim spends something on his family intending to receive Allahâs reward it is regarded as Sadaqa for him.â
Grade: Sahih

Hadith #5220 - Sahih al-Bukhari - Abu Mas'ud al-Ansari (Sahih al-Bukhari)
There was a man called Abu Shuâaib, and he had a slave who was a butcher. He said (to his slave), âPrepare a meal to which I may invite Allahâs Messenger (ï·º) along with four other men.â So he invited Allahâs Messenger (ï·º) and four other men, but another man followed them whereupon the Prophet (ï·º) said, âYou have invited me as one of five guests, but now another man has followed us. If you wish you can admit him, and if you wish you can refuse him.â On that the host said, âB
Grade: Sahih

Hadith #5248 - Sahih al-Bukhari - Abu Mas'ud al-Ansari (Sahih al-Bukhari)
There was an Ansari man nicknamed, Abu Shuâaib, who had a slave who was a butcher. He came to the Prophet (ï·º) while he was sitting with his companions and noticed the signs of hunger on the face of the Prophet (ï·º) . So he went to his butcher slave and said, âPrepare for me a meal sufficient for five persons so that I may invite the Prophet (ï·º) along with four other men.â He had the meal prepared for him and invited him. A (sixth) man followed them. The Prophet (ï·º) said, âO Abu Sh
Grade: Sahih

Hadith #5538 - Sahih al-Bukhari - Abu Mas'ud al-Ansari (Sahih al-Bukhari)
The Prophet (ï·º) forbade the utilization of the price of a dog, the earnings of prostitute and the earnings of a foreteller.
Grade: Sahih

Hadith #5878 - Sahih al-Bukhari - Abu Mas'ud al-Ansari (Sahih al-Bukhari)
A man came to the Prophet (ï·º) and said âI keep away from the morning prayer only because such and such person prolongs the prayer when he leads us in it. The narrator added: I had never seen Allahâs Apostle more furious in giving advice than he was on that day. He said, âO people! There are some among you who make others dislike good deeds) cause the others to have aversion (to congregational prayers). Beware! Whoever among you leads the people in prayer should not prolong it, because am
Grade: Sahih

Hadith #5888 - Sahih al-Bukhari - Abu Mas'ud al-Ansari (Sahih al-Bukhari)
The Prophet (ï·º) said, âOne of the sayings of the early Prophets which the people have got is: If you donât feel ashamed (from Hayaâ: pious shyness from committing religeous indiscretions) do whatever you like.â (See Hadith No 690, 691, Vol 4)
Grade: Sahih

Hadith #6890 - Sahih al-Bukhari - Abu Mas'ud al-Ansari (Sahih al-Bukhari)
A man came to Allahâs Messenger (ï·º) and said, âO Allahâs Messenger (ï·º)! By Allah, I fail to attend the morning congregational prayer because so-and-so (i.e., Mu`adh bin Jabal) prolongs the prayer when he leads us for it.â I had never seen the Prophet (ï·º) more furious in giving advice than he was on that day. He then said, âO people! some of you make others dislike (good deeds, i.e. prayers etc). So whoever among you leads the people in prayer, he should shorten it because among t
Grade: Sahih

Hadith #874 - Sahih Muslim - Abu Mas'ud al-Ansari (Sahih Muslim)
The Messenger of Allah (may peace he upon him) used to touch our shoulders in prayer and say: Keep straight, donât be irregular, for there would be dissension in your hearts. Let those of you who are sedate and prudent be near me, then those who are next to them, then those who are next to them. Abu Masâud said: Now-a-days there is much dissension amongst you.
Grade: Sahih

Hadith #946 - Sahih Muslim - Abu Mas'ud al-Ansari (Sahih Muslim)
A person came to the Messenger of Allah (ï·º) and said: I keep away from the morning prayer on account of such and such (a man), because; he keeps us so long. I never saw Godâs Messenger (ï·º) more angry when giving an exhortation than he was that day. He said: 0 people, some of you are scaring people away. So whoever of you leads the people in prayer he must be brief, for behind him are the weak, the aged, and the people who have (argent) business to attend.
Grade: Sahih

Hadith #1427 - Sahih Muslim - Abu Mas'ud al-Ansari (Sahih Muslim)
The one who is most versed in Allahâs Book should act as Imam for the people, but If they are equally versed in reciting it, then the one who has most knowledge regarding Sunnah if they are equal regarding the Sunnah, then the earliest one to emigrate; it they emigrated at the same time, then the earliest one to embrace Islam. No man must lead another in prayer where (the latter) has authority, or sit in his place of honour in his house, without his permission. Ashajj in his narration used the
Grade: Sahih

Hadith #1429 - Sahih Muslim - Abu Mas'ud al-Ansari (Sahih Muslim)
The Messenger of Allah (ï·º) said to us: The one who is well grounded in Allahâs Book and is distinguished among them in recitation should act as; Imam for the people. and if they are equally versed in reciting it, then the one who has most knowledge regarding Sunnah; if they are equal regarding the Sunnah, then the earliest one to emigrate; If they emigrated at the same time, then the oldest one in age. No man must lead another in prayer in latterâs house or where (the latter) has authority
Grade: Sahih

Hadith #1772 - Sahih Muslim - Abu Mas'ud al-Ansari (Sahih Muslim)
If anyone recites the two verses at the end of Surah al-Baqara at night, they would suffice for him âAbd al-Rahman said: I met Abu Masâud and he was circumambulating the House (of Allah) and asked him about this (tradition) and he narrated it to me from the Messenger of Allah (ï·º).
Grade: Sahih

Hadith #2001 - Sahih Muslim - Abu Mas'ud al-Ansari (Sahih Muslim)
Verily the sun and the moon are the two signs among the signs of Allah by which He frightens his servants and they do not eclipse on account of the death of any one of the people. So when you see anything about them, observe prayer, supplicate Allah till it is cleared from you.
Grade: Sahih

Hadith #2002 - Sahih Muslim - Abu Mas'ud al-Ansari (Sahih Muslim)
Verily the sun and the moon do not eclipse on account of the death of any one of the people, but they are the two signs among the signs of Allah. So when you see it, stand up and observe prayer.
Grade: Sahih

Hadith #2206 - Sahih Muslim - Abu Mas'ud al-Ansari (Sahih Muslim)
When a Muslim spends on his family seeking reward for it from Allah, it counts for him as sadaqa.
Grade: Sahih

Hadith #2239 - Sahih Muslim - Abu Mas'ud al-Ansari (Sahih Muslim)
We were commanded to give charity (despite the fact.) that we were coolies. Abu âAqil donated half a saâ. And there came another man with more than this. The hypocrites said: Verily Allah does not stand in need of the charity of this, and the second one has done nothing but only made a show (of his charity). Then this verse was revealed.â Those who scoff at the voluntary givers of charity among the believers as well as those who cannot find anything (to give) but with their hard labourâ
Grade: Sahih

Hadith #3868 - Sahih Muslim - Abu Mas'ud al-Ansari (Sahih Muslim)
A person from people who lived before you was called to account (by Allah at the Day of Judgment) and no good was found in his account except this that lie being a rich man had (financial) dealings with people and had commanded his servants to show leniency to the straitened ones. Upon this Allah, the Exalted and Majestic, said: We have more right to this, so overlook (his faults).
Grade: Sahih

Hadith #4178 - Sahih Muslim - Abu Mas'ud al-Ansari (Sahih Muslim)
When I was beating my servant, I heard a voice behind me (saying): Abu Masâud, bear in mind Allah has more dominance over you than you have upon him. I turned and (found him) to be Allahâs Messenger (ï·º). I said: Allahâs Messenger, I set him free for the sake of Allah. Thereupon he said: Had you not done that, (the gates of) Hell would have opened for you, or the fire would have burnt you.
Grade: Sahih

Hadith #4179 - Sahih Muslim - Abu Mas'ud al-Ansari (Sahih Muslim)
I seek refuge with Allah, but he continued beating him, whereupon he said: I seek refuge with Allahâs Messenger, and he spared him. Thereupon Allahâs Messenger (ï·º) said: By Allah, God has more dominance over you than you have over him (the slave). He said that he set him free.
Grade: Sahih

Hadith #4762 - Sahih Muslim - Abu Mas'ud al-Ansari (Sahih Muslim)
It is (offered) in the way of Allah. The Messenger of Allah (ï·º) said: For this you will have seven hundred she-camels on the Day of Judgment all of which will be muzzled.
Grade: Sahih

Hadith #4764 - Sahih Muslim - Abu Mas'ud al-Ansari (Sahih Muslim)
A man came to the Messenger of Allah (ï·º) and said: My riding beast has been killed, so give me some animal to ride upon. He (the Holy Prophet) said: I have none with me. A man said: Messenger of Allah, I can guide him to one who will provide him with a riding beast. The Messenger of Allah (ï·º) said: One who guides to something good has a reward similar to that of its doer.
Grade: Sahih

Hadith #5172 - Sahih Muslim - Abu Mas'ud al-Ansari (Sahih Muslim)
0 ye, prepare for us food sufficient for five persons, for I intend to invite Allahâs Apostle (ï·º) who would be the fifth amongst the five. He (the narrator) reported that he then prepared the food and came to Allahâs Apostle (ï·º) and invited all the five (including him) who was the fifth amongst them to the feast. A man followed him and when Allahâs Apostle (ï·º) reached the door, he said: This man has followed us; if you like you may permit him (to join the meal) and if you like he can
Grade: Sahih

Hadith #12 - The Forty Hadith Qudsi - Abu Mas'ud al-Ansari (The Forty Hadith Qudsi)
On the authority of Abu Masâud al-Ansari (may Allah be pleased with him), who said that the Messenger of Allah (may the blessings and peace of Allah be upon him) said: A man from among those who were before you was called to account. Nothing in the way of good was found for him except that he used to have dealings with people and, being well-to-do, he would order his servants to let off the man in straitened circumstances [from repaying his debt]. He (the Prophet p.b.u.h) said that Allah said:
Grade: Sahih